A summary of a survey on proposed African monetary unions - Simplice Asongu; Jacinta C. Nwachukwu; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2017)
This review summarises a survey of about 70 empirical studies on proposed African monetary unions published during the past fifteen years. Four main strands are outlined in four tables. They include the: (i) West African Monetary Zone (WAMZ), (ii) East African Monetary Union (EAMU), (iii) Southern African Monetary Union (SAMU) and (iv) African Monetary Union (AMU). A number of concerns are apparent from the feasibility and/or desirability of potential monetary unions. They are variations in: empirical strategies, selection of variables, considered periodicities and sampled countries. The Hegelian dialectics are used to establish selective expansion as the predominant mode of monetary integration. Some studies make the case for strong institutions and pegs as alternatives to currency unions. The employment of cluster analysis, distinguishing shocks from responses in the examination of business cycle synchronisation and the disaggregation of panels into sub-samples provide more subtle policy implications.
Keywords: F15; F36; F42; O55; P52; 330; Currency Area; Policy Coordination; Africa